A Life at the Intersection of Science and Social Issues. (28th October 2017) - Huston, Aletha C.
Abstract: In this article, I summarize a lifetime of research investigating the socializing effects of contexts outside the family, specifically television, gender‐role expectations, child care, poverty, and public policy. The themes running throughout this work are (a) understanding processes underlying associations of behavior with social and environmental conditions, (b) understanding positive development as well as problem behavior, (c) questioning social values and implicit assumptions in research and policy, and (d) taking a truly interdisciplinary approach. My goals include generating knowledge and applying these themes to policy and practice. I conclude that researchers need to be prepared with good evidence when the policy windows open.